Polymeric monomer for in-situ coating of positive electrode material, and preparation method and application thereof
By coating the sodium electrolaminar oxide positive electrode material by in situ polymerization of monomer compound A, the problem of instability in air is solved, and higher cycling stability and electrochemical properties are achieved.
Patent Information
- Application Number
- CN202411965889.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The sodium-electric layered oxide positive electrode material is unstable in the air and is easily embedded by H2O and CO2, resulting in loss of active sodium, and produces irreversible side reactions, affecting battery performance.
In situ polymerized monomer compound A is used to coat the sodium ion layered oxide positive electrode material to form a dense coating layer to avoid air erosion, and achieve the dual functions of electron conduction and ion conduction through the combination of pyrrole structure and sodium sulfonate.
It improves the cycle stability and life of sodium ion batteries, enhances the air stability of the positive electrode material, reduces side reactions and the loss of active sodium, and improves electrochemical performance.
Smart Images

Figure BDA0005218795120000021 
Figure BDA0005218795120000031 
Figure BDA0005218795120000032
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a polymer monomer for in-situ coating of a positive electrode material, a preparation method and an application thereof. Background Art
[0002] Due to the depletion of fossil energy, the proportion of renewable energy power generation is increasing. However, renewable energy power is generally unstable, and energy storage batteries are needed to balance power peaks and valleys. Although lithium-ion batteries have been widely used in various fields, especially for large-scale energy storage, the low abundance of lithium in the earth's crust makes it unable to meet the increasingly intense demand in the future. As a new energy storage technology, sodium-ion batteries have the advantages of safety, high efficiency, green environmental protection and low cost. They are considered to be a supplement or substitute for lithium-ion batteries and can be promoted and applied in fields such as large-scale energy storage.
[0003] In order to accelerate the development of sodium-ion batteries, exploring cathode materials with excellent performance has always been a research hotspot in this field. In recent years, more and more cathode materials for sodium-ion batteries have been developed. The most studied cathode materials mainly include Prussian blue, polyanions and layered oxides. Among them, layered oxide cathode materials have shown great commercial potential and have received widespread attention due to their high theoretical specific capacity, good conductivity, fast diffusion kinetics, high operating voltage, and easy large-scale production and preparation. However, there are still a series of problems in the widespread application of layered oxide cathode materials, such as poor air stability and easy to be oxidized by H in the air. 2 O and CO 2 The molecules are embedded in the layered structure, thus spontaneously Na + / H + The exchange causes loss of active sodium and forms NaOH and Na 2 CO 3 These electrochemically inactive residual sodium compounds will further cause slurry gelation and current collector corrosion, which is very unfavorable to subsequent electrode manufacturing and battery performance. In addition, when the layered oxide circulates in the electrolyte, a series of interfacial side reactions will occur, leading to irreversible transition metal dissolution and gas release.
[0004] In response to the above-mentioned problems of sodium-electrolyte layered oxide positive electrode materials, the most commonly used method at present is to coat them with a carbon layer, an inorganic solid electrolyte layer and an organic polymer layer to prepare a composite positive electrode material. However, in order to ensure the transmission of sodium ions, the carbon material coating layer is usually a porous layer, which cannot completely isolate the air and achieve the air stability of the active material. The carbon material coating layer is usually used to improve the conductivity of the active material, relying on the exposed positive electrode area of the pores of the coating layer to ensure ion transmission. Compared with the uncoated method, this method limits the ion transmission of the active material to a certain extent. The coating of the inorganic solid electrolyte layer is usually to enhance the transmission of active ions, while maintaining the structural stability when the active ions are deintercalated and the volume changes. Whether it is a simple carbon material coating or an inorganic solid electrolyte coating, in order to ensure the normal electron and ion conduction functions of the active material after coating, the coating layer is a porous layer, which cannot achieve dense coating and realize the air stability of the active material. Summary of the invention
[0005] The purpose of the present invention is to provide a polymer monomer for in-situ coating of a positive electrode material, a preparation method and application thereof. The sodium ion layered oxide positive electrode material of the present invention has good stability, thereby improving the cycle stability and life of the battery.
[0006] The present invention provides a polymer monomer for in-situ coating of a positive electrode material, which has a structure shown in compound A:
[0007]
[0008] In compound A, R 1 It is a C1~C3 alkyl group, n is the degree of polymerization, n=6000~10000.
[0009] Preferably, R 1 -CH 3 、-CH 2 CH 3 、-CH 2 F, -CH 2 OCH 3 、-CH 2 CH 2 F or -CH(CH 3 )2.
[0010] The present invention provides a method for preparing a polymer monomer for in-situ coating of a positive electrode material as described above, comprising the following steps:
[0011] A) mixing compound B and di-tert-butyl dicarbonate in an alcohol solvent, stirring to react, to obtain compound C;
[0012] B) dispersing compound C and zinc chloride in an aprotic solvent, adding hydrochloric acid dropwise, heating and reacting under stirring conditions to obtain compound D;
[0013] C) dispersing compound D in a sodium sulfite aqueous solution, heating the mixture in a first reaction vessel to obtain a mixture containing compound E, then transferring the mixture containing compound E to a second reaction vessel, and dropping trifluoroacetic acid into the mixture, and continuously stirring to react, to obtain compound A;
[0014]
[0015] Preferably, the alcohol solvent in step A) is methanol;
[0016] The reaction temperature in step A) is 40-50° C., and the reaction time in step A) is 1-3 hours.
[0017] Preferably, the aprotic solvent in step B) is one or more of diethyl ether, carbon tetrachloride, dimethyl sulfoxide and acetone;
[0018] The reaction temperature in step B) is 30-50° C., and the reaction time in step B) is 2-6 hours.
[0019] Preferably, in step C), the temperature for reacting compound D with sodium sulfite is 180-220° C., and the reaction time is 2-5 hours;
[0020] The reaction temperature of the mixture containing compound E and trifluoroacetic acid in step C) is 180-220° C. and the reaction time is 1-3 hours.
[0021] The present invention provides an in-situ coated sodium ion positive electrode material, comprising a sodium ion layered oxide positive electrode material and a coating layer coated on the surface of the sodium ion layered oxide;
[0022] The coating layer includes a compound shown in Formula I:
[0023]
[0024] In Formula I, R 1 is a C1-C3 alkyl group, R 2 It is a substituted or unsubstituted C1-C5 alkyl group, and n is the degree of polymerization, n=6000-10000.
[0025] The present invention provides a method for preparing the above-mentioned in-situ coated sodium ion positive electrode material, comprising the following steps:
[0026] a) mixing a sodium ion layered oxide dispersion and a compound A dispersion to perform an in-situ polymerization reaction to obtain an intermediate;
[0027] The sodium ion layered oxide dispersion comprises a sodium ion layered oxide positive electrode material and an inert organic solvent;
[0028] The compound A dispersion comprises compound A, an initiator and an inert organic solvent;
[0029]
[0030] b) the intermediate, R 2 -NH 2 It is mixed with a strong acid resin and modified to obtain an in-situ coated sodium ion positive electrode material.
[0031] Preferably, the molar ratio of the sodium ion layered oxide positive electrode material to compound A is 1:(2-6);
[0032] The temperature of the in-situ polymerization in step A) is 0 to 25° C., and the time of the in-situ polymerization in step A) is 3 to 8 hours;
[0033] The modification temperature in step B) is 75 to 90° C., and the modification time in step B) is 12 to 24 hours.
[0034] The present invention provides a positive electrode, comprising a current collector and a positive electrode active material layer composited on the surface of the current collector, wherein the positive electrode active material layer comprises the in-situ coated sodium ion positive electrode material described above or the in-situ coated sodium ion positive electrode material prepared by the preparation method described above.
[0035] The present invention provides a sodium ion battery, comprising the positive electrode described above.
[0036] The present invention provides a polymer monomer for in-situ coating of anode materials, which has a structure shown in compound A: In compound A, R 1 It is an alkyl group of C1 to C3, n is the degree of polymerization, and n=6000 to 10000. The present invention synthesizes a novel monomer 1-alkyl ketone-2-sodium methanesulfonate-pyrrole compound (compound A), and in-situ coats the sodium electric layer oxygen positive electrode material through polymerization to achieve a dense coating layer, thereby avoiding air erosion of the active material to cause loss of active sodium and improving air stability. By utilizing the electron-conducting properties of the monomer pyrrole structure after polymerization and the active sodium ions in the sodium sulfonate, the dual functions of ion conduction and electron conduction are achieved, ensuring that the composite sodium ion positive electrode material obtained after coating has both high ion conduction ability and good electron conduction ability, which satisfies the ion transmission and electron exchange of the layer oxygen positive electrode material during the charge and discharge process. At the same time, the active sodium ions in the sodium sulfonate can also supplement the active sodium ions of the positive electrode during the cycle.
[0037] In addition, in view of the fact that it is difficult to avoid the transition metal ions in the structure from being released during the ion extraction process and being transferred to the electrolyte through ion transmission, thereby inducing side reactions and leading to rapid consumption of the electrolyte, the present invention further modifies the coating layer on the basis of in-situ coating, and uses alkyl ketones and amino compounds to generate Schiff base structures to anchor the released transition metal ions, inhibit side reactions, and reduce cyclic gas production. This modified polymer coating not only maintains the stability of the electrode material, but also helps to improve the cycle stability and life of the battery. The improved methods of the present invention from multiple angles provide strong technical support for the industrialization and commercial application of sodium ion batteries. DETAILED DESCRIPTION
[0038] The present invention provides a polymer monomer for in-situ coating of a positive electrode material, having a structure shown in compound A:
[0039]
[0040] In compound A, R 1 is a C1-C3 alkyl group, preferably, R 1 -CH 3 、-CH 2 CH 3 、-CH 2 F, -CH 2 OCH 3 、-CH 2 CH 2 F or -CH(CH 3 ) 2 ; n is the degree of polymerization, n=6000~10000, preferably, n is 7000~9000.
[0041] In the present invention, the compound A is one or more of compounds A1 to A6:
[0042]
[0043] The present invention preferably provides a method for preparing the above-mentioned polymer monomer for in-situ coating of positive electrode materials, comprising the following steps:
[0044] A) mixing compound B and di-tert-butyl dicarbonate in an alcohol solvent, stirring to react, to obtain compound C;
[0045] B) dispersing compound C and zinc chloride in an aprotic solvent, adding hydrochloric acid dropwise, heating and reacting under stirring conditions to obtain compound D;
[0046] C) dispersing compound D in a sodium sulfite aqueous solution, heating for reaction, obtaining a mixture containing compound E, then dropping trifluoroacetic acid into the mixture, and continuously stirring for reaction, obtaining compound A;
[0047]
[0048] Specifically, the preparation process of compound A can refer to the reaction formulas shown in formula II to formula III:
[0049]
[0050] The present invention preferably disperses compound B in methanol, and after uniform dispersion, adds a certain amount of di-tert-butyl dicarbonate (Boc 2 O) to protect the pyrrole amino group, stirred at 40-50°C for 1-3h, cooled and passed through a chromatography column to obtain a compound C with a purity of 99%;
[0051] In the present invention, the compound B is preferably a compound represented by any one of formulas B1 to B6:
[0052]
[0053] In the present invention, the compound B and Boc 2 The molar ratio of O is preferably (0.8-1):1, more preferably (0.9-1):1; the reaction temperature is preferably 40-50°C, more preferably 42-48°C, such as 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, preferably a range value with any of the above values as the upper or lower limit; the reaction time is preferably 1-3 hours, more preferably 1-2 hours.
[0054] After obtaining compound C, the present invention preferably dissolves compound C in an aprotic solvent, adds zinc chloride for dispersion, drops hydrochloric acid, heats to 30-50° C., stirs for 2-6 hours, and obtains a mixture containing compound D. The mixture is purified by a chromatography column to obtain compound D with a purity of 99%.
[0055] In the present invention, the aprotic solvent is preferably one or more of ether, carbon tetrachloride, dimethyl sulfoxide and acetone; the molar ratio of zinc chloride to compound C is preferably (1-2):1, more preferably (1.2-1.8):1; the molar ratio of hydrochloric acid to compound C is preferably (1-1.2):1, and the concentration of hydrochloric acid is preferably 0.1-1 mol / L, more preferably 0.5 mol / L; the reaction temperature is preferably 30-50°C, more preferably 35-45°C, such as 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, preferably a range value with any of the above values as the upper or lower limit; the reaction temperature is preferably 2-6 hours, more preferably 3-5 hours.
[0056] After obtaining compound D, the present invention preferably takes a certain amount of compound D and disperses it in a sodium sulfite aqueous solution. After uniform dispersion, the mixed reactant is transferred to a first reaction container, heated to 180-220° C., and reacted for 2-5 hours to obtain a mixture containing compound E, which is transferred to a second reaction container, and then trifluoroacetic acid (TFA) is added dropwise to the mixture, and continuously stirred and reacted for 1-3 hours to obtain a mixture containing compound A, which is purified by a chromatography column to obtain compound A with a purity of 99%.
[0057] In the present invention, the molar ratio of the compound D to sodium sulfite is 1:(1.2-1.8), more preferably 1:(1.3-1.7), most preferably 1:(1.5-1.6), the concentration of the sodium sulfite is preferably 0.1-1 mol / L, more preferably 0.5 mol / L; the molar ratio of the compound D to TFA is preferably 1:(1.2-1.5), more preferably 1:(1.3-1.4); the temperature of the reaction of the compound D with sodium sulfite is preferably 180-220°C, more preferably 190-210°C, such as 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210 ℃, 215℃, 220℃, preferably the range value with any of the above values as the upper or lower limit; the reaction time of the compound D and sodium sulfite is preferably 2 to 5 hours, more preferably 3 to 4 hours; the reaction temperature of the mixture containing compound E and trifluoroacetic acid is preferably 180 to 220℃, more preferably 190 to 210℃, such as 180℃, 185℃, 190℃, 195℃, 200℃, 205℃, 210℃, 215℃, 220℃, preferably the range value with any of the above values as the upper or lower limit; the reaction time of the mixture containing compound E and trifluoroacetic acid is preferably 1 to 3 hours, more preferably 1 to 2 hours. The first reaction vessel is preferably a high-temperature and high-pressure reactor, which can form a closed reaction environment to avoid the reactant solvent with a lower boiling point from evaporating in an open container and taking away the reactant, and the second reaction vessel is preferably a normal pressure reactor.
[0058] The present invention provides an in-situ coated sodium ion positive electrode material, comprising a sodium ion layered oxide positive electrode material and a coating layer coated on the surface of the sodium ion layered oxide positive electrode material;
[0059] The coating layer comprises a compound shown in formula I,
[0060]
[0061] In Formula I, R 1 is a C1-C3 alkyl group, R 2 It is a substituted or unsubstituted C1-C5 alkyl group, and n is the degree of polymerization, n=6000-10000.
[0062] In the present invention, the sodium ion layered oxide may have a structural formula of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 .
[0063] In the present invention, the coating layer comprises a compound shown in Formula I, wherein the compound shown in Formula I is obtained by in-situ polymerization of a compound A and then reacting with an amino compound (R 2-NH 2 ) modified.
[0064] In Formula I, R 1 is a C1-C3 alkyl group, such as methyl, ethyl, propyl or isopropyl. Preferably, R 1 -CH 3 、-CH 2 CH 3 、-CH 2 F, -CH 2 OCH 3 、-CH 2 CH 2 F or -CH(CH 3 ) 2 ; R 2 is a substituted or unsubstituted C1-C5 alkyl group, preferably an unsubstituted C1-C5 alkyl group, a halogen-substituted C1-C5 alkyl group or an alkoxy-substituted C1-C5 alkyl group, more preferably, R 2 -CH 2 CH 3 、-CH 2 CH 2 CH 3 、-CH 2 OCH 3 、-CH 2 CH 2 CHCH 3 F, -CH 2 CH 2 OCH 3 or -CH 2 OCH(CH 3 ) 2 n is the degree of polymerization, n=6000-10000, preferably, n is 7000-9000.
[0065] In the present invention, the coating layer is a polymer coating layer obtained by in-situ polymerization of monomer compound A on the surface of the sodium ion layered oxide and then modification with an amino compound. The thickness of the coating layer is preferably 0.01 to 0.2 μm, more preferably 0.05 to 0.15 μm.
[0066] The present invention also provides a method for preparing the above-mentioned in-situ coated sodium ion positive electrode material, comprising the following steps:
[0067] a) mixing a sodium ion layered oxide dispersion and a compound A dispersion to perform an in-situ polymerization reaction to obtain an intermediate;
[0068] The sodium ion layered oxide dispersion comprises a sodium ion layered oxide and an inert organic solvent;
[0069] The compound A dispersion comprises compound A, an initiator, a catalyst and an inert organic solvent;
[0070]
[0071] b) the intermediate, R 2 -NH 2 It is mixed with a strong acid resin and modified to obtain a sodium ion layered oxide positive electrode material.
[0072] In the present invention, the structure and preparation method of the compound A are consistent with the structure and preparation method of the compound A described above, and the present invention will not be repeated here.
[0073] After obtaining compound A, the present invention mixes the compound A with an inert organic solvent, stirs for 1 to 3 hours to fully dissolve compound A, then adds an initiator and a catalyst, continues stirring, and obtains a dispersion of compound A after it is fully dissolved.
[0074] In the present invention, the inert organic solvent is preferably an anhydrous or low water-active organic solvent, more preferably dichloromethane and / or chloroform; the initiator is preferably ferric chloride (FeCl 3 ), the catalyst is preferably boron trifluoride etherate (BF3·OEt 2 ) and / or p-toluenesulfonic acid (TsOH); the molar ratio of the initiator to compound A is preferably (0.01-0.1):1, more preferably (0.03-0.08):1, such as 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, preferably a range value with any of the above values as the upper or lower limit; the molar ratio of the catalyst to compound A is preferably (0.001-0.01):1, more preferably (0.003-0.008):1, such as 0.001:1, 0.003:1, 0.005:1, 0.007:1, 0.008:1, 0.01:1, preferably a range value with any of the above values as the upper or lower limit.
[0075] The invention mixes sodium ion layered oxide with an inert organic solvent, stirs and uniformly disperses the mixture in the organic solvent, and obtains a sodium ion layered oxide dispersion.
[0076] In the present invention, the inert organic solvent is preferably an anhydrous or low water-active organic solvent, more preferably dichloromethane and / or chloroform; the inert organic solvent used in the sodium ion layered oxide dispersion and the inert organic solvent used in the compound A dispersion may be of the same or different type, preferably using the same type of inert organic solvent.
[0077] In the present invention, the molar ratio of the sodium ion layered oxide to compound A is preferably 1:(2-6), more preferably 1:(3-5), such as 1:2, 1:3, 1:4, 1:5, 1:6, preferably a range value with any of the above values as the upper or lower limit.
[0078] After obtaining the sodium ion layered oxide dispersion and the compound A dispersion, the present invention mixes the two and performs an in-situ polymerization reaction as shown in formula IV. After the reaction is completed, the reactants are filtered, washed and dried to obtain the sodium ion layered oxide coated with polymer A.
[0079]
[0080] In the present invention, the temperature of the in-situ polymerization reaction is preferably 0-25°C, more preferably 5-20°C, such as 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, preferably a range value with any of the above values as the upper or lower limit; the time of the in-situ polymerization reaction is preferably 3-8 hours, more preferably 4-6 hours.
[0081] In the present invention, the drying temperature is preferably 40-45°C, such as 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, preferably a range value with any of the above values as the upper or lower limit; the drying time is preferably 2-6h, more preferably 3-5h.
[0082] In order to further inhibit the dissolution of transition metal ions during the circulation process, the present invention obtains a sodium ion layered oxide coated with polymer A, a strong acid resin and R 2 -NH 2 The mixture is mixed and subjected to a modification reaction as shown in Formula V to obtain a sodium ion layered oxide positive electrode material.
[0083]
[0084] In the present invention, the strong acid resin is preferably a strong acid gel resin; 2 -NH 2 Preferably, it has a structure shown in any one of Formula VI to Formula XI,
[0085]
[0086] In the present invention, the polymer A and R 2 -NH 2The molar ratio of the polymer A to the strong acid resin is preferably 1:(1.1-2), more preferably 1:(1.2-1.8), such as 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, preferably a range value with the above arbitrary numerical value as the upper or lower limit; the molar ratio of the polymer A to the strong acid resin is preferably 1:(0.01-0.05), more preferably 1:(0.02-0.04), such as 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, preferably a range value with the above arbitrary numerical value as the upper or lower limit.
[0087] In the present invention, the temperature of the modification reaction is preferably 75 to 90° C., more preferably 80 to 85° C., and the time of the modification reaction is preferably 12 to 24 hours, more preferably 16 to 18 hours.
[0088] The present invention also provides another in-situ coated sodium ion positive electrode material, comprising a sodium ion layered oxide positive electrode material and a coating layer (unmodified) coated on the surface of the sodium ion layered oxide positive electrode material;
[0089] The coating (unmodified) comprises polymer A,
[0090]
[0091] In the present invention, the type of the sodium ion layered oxide and the values of n and R1 in polymer A are consistent with the type of the sodium ion layered oxide and the values of n and R1 in polymer A described above, and the present invention will not be repeated here.
[0092] The coating layer (unmodified) includes polymer A, and the polymer A is formed by in-situ polymerization of compound A on the surface of sodium ion layered oxide.
[0093] In the present invention, the method for preparing the in-situ coated sodium ion positive electrode material with an unmodified coating layer is consistent with the method for preparing the sodium ion layered oxide coated with polymer A in step a) of the method for preparing the in-situ coated sodium ion positive electrode material described above, and the present invention will not be repeated here.
[0094] The present invention also provides a positive electrode, comprising a current collector and a positive electrode active material layer composited on the surface of the current collector, wherein the positive electrode active material layer comprises any one or two of the two in-situ coated sodium ion positive electrode materials described above.
[0095] In the present invention, the positive electrode active material layer also includes a conductive agent and a binder. The present invention has no special restrictions on the types of the conductive agent and the binder. The conductive agent and the binder commonly used in the positive electrode of the sodium ion battery in the field can be used. For example, the conductive agent can be conductive carbon black SP, and the binder can be PVDF.
[0096] The present invention mixes the above-mentioned in-situ coated sodium ion positive electrode material, conductive agent, binder and solvent, controls the solid content to be 65-75%, preferably 70%, fully stirs to obtain positive electrode slurry, and then coats the positive electrode slurry on the surface of a current collector such as aluminum foil, and obtains the positive electrode after drying.
[0097] The present invention also provides a sodium ion battery, comprising the positive electrode, negative electrode, separator and electrolyte described above.
[0098] In the present invention, the separator is preferably a polypropylene (PP) or polyethylene (PE) separator; the negative electrode material is selected from a hard carbon negative electrode; and the electrolyte comprises a sodium salt, a non-aqueous organic solvent and an additive.
[0099] In the present invention, the sodium salt is preferably sodium hexafluorophosphate (NaPF 6 ), perchloric acid (NaClO 4 ), sodium tetrafluoroborate (NaBF 4 ), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonyl imide (NaFSI) and sodium difluorooxalate borate (NaODFB), preferably NaPF 6 and / or NaFSI; the mass fraction of the sodium salt in the electrolyte raw material is preferably 12-16%, more preferably 13-15%.
[0100] In the present invention, the non-aqueous organic solvent is preferably one or more of organic esters, C1-10 alkyl ethers, cyclic ethers, sulfones and dinitriles; the organic esters are preferably at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), methyl formate (MF), ethyl acetate (EA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), butyl propionate (BP) and ethyl butyrate (EB); the C1-10 alkyl ethers are at least one of dimethyl ether, diethyl ether and methyl ethyl ether; the dinitriles are at least one of adiponitrile, succinonitrile and glutaronitrile; the sulfones are at least one of dimethyl sulfoxide and cyclopentane sulfone; the mass fraction of the non-aqueous organic solvent in the electrolyte raw material is preferably 77-85%, more preferably 80-82%.
[0101] In the present invention, the additive includes one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), diethylene sulfate (DTD), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), 1,4-butane sultone (BS), tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB) and succinic anhydride (SA); the mass fraction of the additive in the electrolyte raw material is preferably 1-6%, more preferably 2-5%.
[0102] Compared with the prior art, the present invention has the following advantages:
[0103] (1) Through in-situ polymerization coating, the sodium layered oxide active material is densely coated to avoid air erosion, achieve air stability of the sodium layered oxide active material, and inhibit the side reaction of the electrolyte on the surface of the active material during the electrochemical process, inhibiting gas production. In addition, through polymer coating, it can well adapt to the volume change caused by the active ion deintercalation process, inhibit the structural collapse caused by phase change, and maintain the structural stability of the cycle process.
[0104] (2) The sodium-ion layered oxide positive electrode material is coated with a polymer having both electrical and ion conductivity as shown in Formula I, thereby ensuring that the coated composite positive electrode active material has both high electrical and ion conductivity, achieving better electrochemical performance, inhibiting the charge and discharge process of the sodium-ion layered oxide positive electrode, and thereby improving the cycle performance.
[0105] (3) The sodium sulfonate on the ion-conducting side chain of the compound represented by Formula I in the coating layer is an active sodium ion, which can achieve the high ion-conducting performance of the coating layer while achieving the role of sodium supplementation in the positive electrode, thereby further improving the cycle life.
[0106] (4) The Schiff base structure in the compound represented by Formula I in the coating layer can coordinate well with the transition metal ions, thereby anchoring the transition metal ions and preventing the transition metal ions from transferring to the negative electrode to catalyze the decomposition of the electrolyte. The side reactions caused by the transition metal ions are suppressed by the double confinement effect of the coating layer and the coating surface layer.
[0107] In order to further illustrate the present invention, a polymer monomer for in-situ coating of positive electrode materials, a preparation method thereof and applications provided by the present invention are described in detail below in combination with embodiments, but it should not be construed as limiting the scope of protection of the present invention.
[0108] Example 1
[0109] Preparation of Compound I
[0110] Reaction 1
[0111]
[0112] Reaction 2
[0113]
[0114] 1. Disperse 15 mmol of compound B1 in 200 ml of methanol, and add 15 mmol of di-tert-butyl dicarbonate (Boc 2 O), stirred at 40°C for 3h, cooled and passed through a chromatography column to obtain compound C with a purity of 99% and a yield of 60.2%. GC-MS (m / z): calcd.for C 12 H 17 O 4 N,239.27,found239.56.
[0115] 2. Dissolve 10 mmol of compound C in 150 ml of ether, add 10 mmol of zinc chloride for dispersion, add 20 ml of hydrochloric acid dropwise, heat to 30°C, stir for 6 hours to obtain a mixture containing compound D, purify the mixture by chromatography column to obtain compound D with a purity of 99% and a yield of 63.4%. GC-MS (m / z): calcd.for C 12 H 16 O 3 ClN,257.71,found257.92;
[0116] 3. Take 10 mmol of compound D and disperse it in 24 ml of sodium sulfite aqueous solution. After uniform dispersion, transfer it to a reactor and heat it to 200 ° C. React for 4 hours to obtain a mixture containing compound E. Then, 12 mmol of TFA is added dropwise to the mixture, and the mixture is continuously stirred and reacted for 2 hours to obtain a mixture containing compound A. Purify it with a chromatography column to obtain compound I with a purity of 99% and a yield of 62.7%. GC-MS (m / z): calcd. for NaC 7 H 8 O 4 NS,225.19,found 225.63.
[0117] Preparation of in-situ coated sodium ion layered oxide positive electrode material and sodium ion layered oxide positive electrode sheet
[0118] Reaction 1
[0119]
[0120] 1. 2 mol of sodium ion layered oxide positive electrode active material (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2) is dispersed in dichloromethane and stirred continuously to make the positive electrode material uniformly dispersed in the solvent;
[0121] 2. Then, 6 mol of compound I was dissolved in dichloromethane and stirred for 1.5 h to fully dissolve compound I. After compound I was dissolved, 0.12 mol of initiator ferric chloride (FeCl 3 ) and 0.006 mol of catalyst boron trifluoride etherate (BF 3 ·OEt 2 ), and continue stirring to fully dissolve;
[0122] 3. Mix the positive electrode material dispersion and the compound I solution, stir evenly, control the temperature at 10° C., react for 6 hours, filter, wash and dry the reaction mixture to obtain a sodium ion layered oxide positive electrode material 1 coated with polymer I.
[0123] 4. The sodium ion layered oxide positive electrode material 1 coated with polymer I prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is applied to aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0124] Preparation of electrolyte 1 sample
[0125] In an argon glove box with a water and oxygen content of ≤0.1 ppm, ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) were uniformly mixed to obtain an organic solvent, and then sodium hexafluorophosphate (NaPF 6 ), sodium trifluoromethanesulfonimide (NaFSI), after being completely dissolved, add fluoroethylene carbonate (FEC) and vinylene carbonate (VC), stir evenly to obtain electrolyte 1, wherein NaPF 6 , NaFSI, EC, DEC, EMC, FEC and VC usage are 13%, 1%, 20%, 13%, 50%, 2% and 1% of the total mass of the electrolyte, respectively.
[0126] Preparation of experimental battery 1 sample
[0127] 1. Mix the hard carbon negative electrode, conductive agent carbon black (SuperP), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) in a mass ratio of 96.3:1.2:1:1.5. After mixing, add N-methylpyrrolidone to control the theoretical solid content to 50%. Use a vacuum defoamer to homogenize to obtain a negative electrode slurry, and evenly coat the negative electrode slurry on an aluminum foil with a thickness of 17 μm. After drying, rolling, and cutting, a 58 mm × 76 mm negative electrode sheet is obtained.
[0128] 2. Make soft-pack laminated batteries at an ambient dew point of ≤-45°C, stack the coated modified positive electrode sheet, PE diaphragm, and negative electrode sheet in sequence, with the positive and negative electrode tabs on the same side, so that the diaphragm is placed between the positive and negative electrode sheets to play an isolating role, and obtain a bare battery cell.
[0129] 3. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, and then inject the prepared electrolyte 1 sample after cooling to below 40°C to obtain an experimental battery 1 sample, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0130] Example 2
[0131] Preparation of Compound II
[0132] Compound B2 was prepared according to reaction formula 1 (referenced from the literature "One-Step Synthesis of 3-Aryl-and3,4-Diaryl-(1H)-Pyrroles Using Tosylmethyl Isocyanide (TOSMIC)"), Ar1 is -CH 2 OH, Ar2 is -COCH 2 CH 3 .
[0133] Reaction 1
[0134]
[0135] Reaction 2
[0136]
[0137] Reaction 3
[0138]
[0139] 1. Disperse 20 mmol of compound B2 in 250 ml of methanol. After uniform dispersion, add 25 mmol of di-tert-butyl dicarbonate (Boc 2 O), stirred at 45°C for 2h, cooled and passed through a chromatography column to obtain compound C2 with a purity of 99% and a yield of 62.7%. GC-MS (m / z): calcd.for C 13 H 19 O 4 N,253.3,found253.46.
[0140] 2. Dissolve 10 mmol of compound C2 in 150 ml of carbon tetrachloride, add 12 mmol of zinc chloride for dispersion, add 22 ml of hydrochloric acid dropwise, heat to 35°C, stir for 5 h, and obtain a mixture containing compound D2. Purify the mixture by chromatography to obtain compound D2 with a purity of 99% and a yield of 63.4%. GC-MS (m / z): calcd.for C 13 H 18 O 3 ClN,271.74,found272.05;
[0141] 3. Take 10 mmol of compound D2 and disperse it in 28 ml of sodium sulfite aqueous solution. After uniform dispersion, transfer it to a reactor and heat it to 180°C. React for 5 hours to obtain a mixture containing compound E2. Then, add 13 mmol of TFA dropwise to the mixture and continue stirring. React for 3 hours to obtain a mixture containing compound II. Purify it with a chromatography column to obtain compound II with a purity of 99% and a yield of 61.3%. GC-MS (m / z): calcd. for NaC 8 H 10 O 4 NS,239.22,found239.41.
[0142] Preparation of in-situ coated sodium ion layered oxide positive electrode material and sodium ion layered oxide positive electrode sheet reaction formula 1
[0143]
[0144] 1. 2 mol of sodium ion layered oxide positive electrode active material (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 ) is dispersed in dichloromethane and stirred continuously to make the positive electrode material uniformly dispersed in the solvent;
[0145] 2. Then, 4 mol of compound II was dissolved in dichloromethane and stirred for 1 hour to fully dissolve compound II. After compound II was dissolved, 0.04 mol of initiator ferric chloride (FeCl 3 ) and 0.012 mol of catalyst p-toluenesulfonic acid (TsOH), and continue stirring to fully dissolve;
[0146] 3. Mix the positive electrode material dispersion and compound II solution, stir evenly, control the temperature at 20°C, react for 3 hours, filter, wash and dry the reaction mixture to obtain a sodium ion layered oxide positive electrode material 2 coated with polymer II.
[0147] 4. The sodium ion layered oxide positive electrode material 2 coated with polymer II prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is coated on aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0148] Preparation of electrolyte 2 samples
[0149] In an argon glove box with a water and oxygen content of ≤0.1 ppm, ethylene carbonate (EC), propylene carbonate (PC), and ethyl methyl carbonate (EMC) were uniformly mixed to obtain an organic solvent, and then sodium hexafluorophosphate (NaPF 6 ), sodium trifluoromethanesulfonimide (NaFSI), after being completely dissolved, add fluoroethylene carbonate (FEC) and vinylene carbonate (VC), stir evenly to obtain electrolyte 1, wherein NaPF 6 , NaFSI, PC, DEC, EMC, FEC and VC usage are 13%, 1%, 20%, 13%, 50%, 2% and 1% of the total mass of the electrolyte, respectively.
[0150] Preparation of experimental battery 2 samples
[0151] 1. The preparation of negative electrode sheets and the assembly of bare cells are the same as those in Example 1.
[0152] 2. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, and then inject the prepared polymer precursor electrolyte 2 after cooling to below 40°C to obtain the experimental battery 2 sample, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0153] Example 3
[0154] Preparation of Compound III
[0155] Compound B3 was prepared according to reaction formula 1 (referenced from the literature "One-Step Synthesis of 3-Aryl-and3,4-Diaryl-(1H)-Pyrroles Using Tosylmethyl Isocyanide (TOSMIC)"), Ar 1 -CH 2 OH, Ar 2 For-COCH 2 F.
[0156] Reaction 1
[0157]
[0158] Reaction 2
[0159]
[0160] Reaction 3
[0161]
[0162] 1. Disperse 18 mmol of compound B3 in 250 ml of methanol, add 20 mmol of di-tert-butyl dicarbonate (Boc2O) after uniform dispersion, stir at 50°C for 1 hour, cool and pass through a chromatography column to obtain compound C3 with a purity of 99% and a yield of 60.2%. GC-MS (m / z): calcd.for C 12 H 16 O 4 FN,257.26,found 257.8.
[0163] 2. Dissolve 10 mmol of compound C2 in 150 ml of dimethyl sulfoxide, add 15 mmol of zinc chloride for dispersion, add 24 ml of hydrochloric acid dropwise, heat to 45°C, stir for 3 h, and obtain a mixture containing compound D3. Purify the mixture by chromatography to obtain compound D3 with a purity of 99% and a yield of 61.5%. GC-MS (m / z): calcd.for C 12 H 15 O 3 ClFN,275.7,found276.05;
[0164] 3. Take 10 mmol of compound D3 and disperse it in 30 ml of sodium sulfite aqueous solution. After uniform dispersion, transfer it to a reactor and heat it to 220° C. to react for 2 h to obtain a mixture containing compound E3. Then, 15 mmol of TFA is added dropwise to the mixture and stirred continuously for 1 h to obtain a mixture containing compound III. Purify it with a chromatography column to obtain compound III with a purity of 99% and a yield of 62.8%. GC-MS (m / z): calcd. for NaC 7 H 7 O 4 FNS,243.18,found243.69.
[0165] Preparation of in-situ coated sodium ion layered oxide positive electrode material and sodium ion layered oxide positive electrode sheet reaction formula 1
[0166]
[0167] 1. 2 mol of sodium ion layered oxide positive electrode active material (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2) is dispersed in chloroform and stirred continuously to make the positive electrode material uniformly dispersed in the solvent;
[0168] 2. Then, 10 mol of compound II was dissolved in chloroform and stirred for 3 h to fully dissolve compound II. After compound III was dissolved, 1 mol of initiator ferric chloride (FeCl 3 ) and 0.05 mol of catalyst boron trifluoride etherate (BF 3 ·OEt 2 ) and continue stirring to fully dissolve;
[0169] 3. Mix the positive electrode material dispersion with the compound III solution, stir evenly, control the temperature at 15°C, react for 4.5 hours, filter, wash and dry the reaction mixture to obtain a sodium ion layered oxide positive electrode material coated with polymer III.
[0170] 4. The sodium ion layered oxide positive electrode material 3 coated with polymer III prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is coated on aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0171] Prepare the electrolyte 3 sample, the specific steps are as follows:
[0172] In an argon glove box with a water and oxygen content of ≤0.1 ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) were uniformly mixed to obtain an organic solvent, and then sodium hexafluorophosphate (NaPF 6 ), sodium trifluoromethanesulfonimide (NaFSI), after being completely dissolved, fluoroethylene carbonate (FEC) and vinylene carbonate (VC) were added, and the electrolyte 3 was obtained after stirring evenly, wherein NaPF 6 , NaFSI, EC, PC, DEC, DMC, FEC and VC usage are 13.5%, 1.5%, 25%, 8%, 16%, 30%, 5% and 1% of the total mass of the electrolyte, respectively.
[0173] Preparation of experimental battery 3 samples
[0174] 1. The preparation of negative electrode sheets and the assembly of bare cells are the same as those in Example 1.
[0175] 2. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, and then inject the prepared polymer precursor electrolyte 3 after cooling to below 40°C to obtain the experimental battery 3 sample, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0176] Example 4
[0177] Preparation of Compound IV
[0178] Compound B4 was prepared according to reaction formula 1 (referenced from the literature "One-Step Synthesis of 3-Aryl-and3,4-Diaryl-(1H)-Pyrroles Using TosylmethylIsocyanide (TOSMIC)"), Ar 1 -CH 2 OH, Ar 2 For-COCH 2 OCH 3 .
[0179] Reaction 1
[0180]
[0181] Reaction 2
[0182]
[0183] Reaction 3
[0184]
[0185] 1. Disperse 17 mmol of compound B4 in 250 ml of methanol, and add 20 mmol of di-tert-butyl dicarbonate (Boc 2 O), stirred at 42°C for 2.5h, cooled and passed through a chromatography column to obtain compound C4 with a purity of 99% and a yield of 63.4%. GC-MS (m / z): calcd.for C 13 H 19 O 5 N,269.3,found 269.48.
[0186] 2. Dissolve 10 mmol of compound C4 in 150 ml of acetone, add 20 mmol of zinc chloride for dispersion, add 24 ml of hydrochloric acid dropwise, heat to 50°C, stir for 2.5 h to obtain a mixture containing compound D4, purify the mixture by chromatography column to obtain compound D4 with a purity of 99% and a yield of 60.5%. GC-MS (m / z): calcd.for C 13 H 18 O 4 ClN,287.74,found288.15;
[0187] 3. Take 10 mmol of compound D4 and disperse it in 36 ml of sodium sulfite aqueous solution. After uniform dispersion, transfer it to a reactor and heat it to 210° C. to react for 3 h to obtain a mixture containing compound E4. Then, 14 mmol of TFA is added dropwise to the mixture and stirred continuously. The mixture is reacted for 1.8 h to obtain a mixture containing compound IV. The mixture is purified by chromatography to obtain compound IV with a purity of 99% and a yield of 62.8%. GC-MS (m / z): calcd. for NaC 8 H 10 O 5 NS,255.22,found255.41.
[0188] Preparation of in-situ coated sodium ion layered oxide positive electrode material and sodium ion layered oxide positive electrode sheet
[0189] Reaction 1
[0190]
[0191] 1. 2 mol of sodium ion layered oxide positive electrode active material (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 ) is dispersed in chloroform and stirred continuously to make the positive electrode material uniformly dispersed in the solvent;
[0192] 2. Then, 12 mol of compound IV was dissolved in chloroform and stirred for 2.5 h to fully dissolve compound II. After compound IV was dissolved, 0.96 mol of initiator ferric chloride (FeCl 3 ) and 0.12 mol of catalyst boron trifluoride etherate (BF 3 ·OEt 2 ) and continue stirring to fully dissolve;
[0193] 3. Mix the positive electrode material dispersion and compound IV solution, stir evenly, control the temperature at 5°C, react for 7 hours, filter, wash and dry the reaction mixture to obtain a sodium ion layered oxide positive electrode material 4 coated with polymer IV.
[0194] 4. The sodium ion layered oxide positive electrode material 4 coated with polymer IV prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is coated on aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0195] Preparation of electrolyte 4 samples
[0196] In an argon glove box with a water and oxygen content of ≤0.1 ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) were uniformly mixed to obtain an organic solvent, and then sodium hexafluorophosphate (NaPF 6 ), sodium trifluoromethanesulfonimide (NaFSI), after being completely dissolved, fluoroethylene carbonate (FEC) and vinylene carbonate (VC) were added, and the electrolyte 3 was obtained after stirring evenly, wherein NaPF 6 , NaFSI, EC, PC, DEC, DMC, FEC and VC usage are 14.5%, 1.5%, 25%, 5%, 20%, 30%, 3% and 1% of the total mass of the electrolyte, respectively.
[0197] Preparation of experimental battery 4 samples
[0198] 1. The preparation of negative electrode sheets and the assembly of bare cells are the same as those in Example 1.
[0199] 2. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, and then inject the prepared polymer precursor electrolyte 4 after cooling to below 40°C to obtain an experimental battery 4 sample, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0200] Example 5
[0201] Preparation of Compound V
[0202] Compound B5 was prepared according to reaction formula 1 (referenced from the literature "One-Step Synthesis of 3-Aryl-and3,4-Diaryl-(1H)-Pyrroles Using Tosylmethyl Isocyanide (TOSMIC)"), Ar 1 -CH 2 OH, Ar 2 For-COCH 2 CH 2 F.
[0203] Reaction 1
[0204]
[0205] Reaction 2
[0206]
[0207] Reaction 3
[0208]
[0209] 1. Disperse 12 mmol of compound B5 in 250 ml of methanol, and add 15 mmol of di-tert-butyl dicarbonate (Boc 2 O), stirred at 46 ° C for 1.8 h, cooled and passed through a chromatography column to obtain compound C5 with a purity of 99% and a yield of 61.3%. GC-MS (m / z): calcd.for C 13 H 18 O 4 FN,271.29,found 271.46.
[0210] 2. Dissolve 10 mmol of compound C5 in 150 ml of ether, add 16 mmol of zinc chloride for dispersion, add 22 ml of hydrochloric acid dropwise, heat to 40°C, stir for 3.5 h to obtain a mixture containing compound D5, purify the mixture by chromatography column to obtain compound D5 with a purity of 99% and a yield of 61.3%. GC-MS (m / z): calcd.for C 13 H 17 O 3 ClFN,289.73,found289.95;
[0211] 3. Take 10 mmol of compound D5 and disperse it in 32 ml of sodium sulfite aqueous solution. After uniform dispersion, transfer it to a reactor and heat it to 190° C. for 3.5 h to obtain a mixture containing compound E5. Then, 13 mmol of TFA is added dropwise to the mixture and stirred continuously for 2.4 h to obtain a mixture containing compound V. Purify it with a chromatography column to obtain compound V with a purity of 99% and a yield of 64.1%. GC-MS (m / z): calcd. for NaC 8 H 9 O 4 FNS,257.21,found 257.61.
[0212] Preparation of in-situ coated sodium ion layered oxide positive electrode material and sodium ion layered oxide positive electrode sheet reaction formula 1
[0213]
[0214] 1. 2 mol of sodium ion layered oxide positive electrode active material (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 ) is dispersed in dichloromethane and stirred continuously to make the positive electrode material uniformly dispersed in the solvent;
[0215] 2. Then, 8 mol of compound V was dissolved in dichloromethane and stirred for 1 h to fully dissolve compound V. After compound V was dissolved, 0.48 mol of initiator ferric chloride (FeCl3 ) and 0.056 mol of catalyst p-toluenesulfonic acid (TsOH) and continued stirring to fully dissolve;
[0216] 3. Mix the positive electrode material dispersion and the compound V solution, stir evenly, control the temperature at 0°C, react for 8 hours, filter, wash and dry the reaction mixture to obtain a sodium ion layered oxide positive electrode material 5 coated with polymer V.
[0217] 4. The sodium ion layered oxide positive electrode material 5 coated with polymer V prepared above is mixed with conductive agent SP, binder PVDF and solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is coated on aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0218] Preparation of electrolyte 5 samples
[0219] In an argon glove box with a water and oxygen content of ≤0.1 ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and diethyl carbonate (EMC) were uniformly mixed to obtain an organic solvent, and then sodium hexafluorophosphate (NaPF 6 ), after being completely dissolved, fluoroethylene carbonate (FEC) and vinylene carbonate (VC) were added, and the electrolyte 5 was obtained after stirring evenly, wherein NaPF 6 The usage amounts of EC, PC, DEC, EMC, FEC and VC are 12%, 15%, 5%, 20%, 44%, 2.5% and 1.5% of the total mass of the electrolyte respectively.
[0220] Preparation of experimental battery 5 samples
[0221] 1. The preparation of negative electrode sheets and the assembly of bare cells are the same as those in Example 1.
[0222] 2. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, and then inject the prepared polymer precursor electrolyte 5 after cooling to below 40°C to obtain an experimental battery 5 sample, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0223] Example 6
[0224] Preparation of Compound VI
[0225] Compound B6 was prepared according to reaction formula 1 (referenced from the literature "One-Step Synthesis of 3-Aryl-and3,4-Diaryl-(1H)-Pyrroles Using Tosylmethyl Isocyanide (TOSMIC)"), Ar 1 -CH 2 OH, Ar 2 -CO(CH 3 ) 2 .
[0226] Reaction 1
[0227]
[0228] Reaction 2
[0229]
[0230] Reaction 3
[0231]
[0232] 1. Disperse 12 mmol of compound B6 in 250 ml of methanol, and add 12 mmol of di-tert-butyl dicarbonate (Boc 2 O), stirred at 48 ° C for 1.2 hours, cooled and passed through a chromatography column to obtain compound C6 with a purity of 99% and a yield of 60.2%. GC-MS (m / z): calcd.for C 14 H 21 O 4 N,267.32,found 267.46.
[0233] 2. Dissolve 10 mmol of compound C6 in 150 ml of ether, add 18 mmol of zinc chloride for dispersion, add 20 ml of hydrochloric acid dropwise, heat to 50°C, stir for 2.5 h to obtain a mixture containing compound D6, purify the mixture by chromatography column to obtain compound D6 with a purity of 99% and a yield of 63.2%. GC-MS (m / z): calcd.for C 14 H 20 O 3 ClN,285.77,found285.95;
[0234] 3. Take 10 mmol of compound D6 and disperse it in 24 ml of sodium sulfite aqueous solution. After uniform dispersion, transfer it to a reactor and heat it to 205° C. for 3.5 h to obtain a mixture containing compound E6. Then, 12 mmol of TFA was added dropwise to the mixture and stirred continuously for 1.4 h to obtain a mixture containing compound V. After purification by chromatography, compound VI with a purity of 99% was obtained, with a yield of 62.1%. GC-MS (m / z): calcd. for NaC 9 H 12 O 4 NS,253.52,found 253.8.
[0235] Preparation of in-situ coated sodium ion layered oxide positive electrode material and sodium ion layered oxide positive electrode sheet reaction formula 1
[0236]
[0237] 1. 2 mol of sodium ion layered oxide positive electrode active material (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 ) is dispersed in chloroform and stirred continuously to make the positive electrode material uniformly dispersed in the solvent;
[0238] 2. Then, 4 mol of compound VI was dissolved in chloroform and stirred for 2.2 h to fully dissolve compound VI. After compound VI was dissolved, 0.16 mol of initiator ferric chloride (FeCl 3 ) and 0.04 mol of catalyst p-toluenesulfonic acid (TsOH) and continue stirring to fully dissolve;
[0239] 3. Mix the positive electrode material dispersion and the compound VI solution, stir evenly, control the temperature at 15° C., react for 4 hours, filter, wash and dry the reaction mixture to obtain a sodium ion layered oxide positive electrode material 6 coated with polymer VI.
[0240] 4. The sodium ion layered oxide positive electrode material 6 coated with polymer V prepared above is mixed with conductive agent SP, binder PVDF and solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is coated on aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0241] Preparation of electrolyte 6 samples
[0242] In an argon glove box with a water and oxygen content of ≤0.1 ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and diethyl carbonate (EMC) were uniformly mixed to obtain an organic solvent, and then sodium hexafluorophosphate (NaPF 6 ), sodium trifluoromethanesulfonimide (NaFSI), and after it is completely dissolved, fluoroethylene carbonate (FEC) is added, and the electrolyte 3 is obtained after stirring evenly, wherein NaPF 6 , NaFSI, EC, PC, DEC, EMC and VC usage are 13%, 1%, 15%, 5%, 20%, 45% and 1% of the total mass of the electrolyte, respectively.
[0243] Preparation of experimental battery 6 samples
[0244] 1. The preparation of negative electrode sheets and the assembly of bare cells are the same as those in Example 1.
[0245] 2. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, and then inject the prepared polymer precursor electrolyte 6 after cooling to below 40°C to obtain an experimental battery 6 sample, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0246] Example 7
[0247] Preparation of modified in-situ coated sodium ion layered oxide cathode materials
[0248] Reaction 1
[0249]
[0250] 1. The sodium ion layered oxide positive electrode material 1 coated with polymer I obtained in Example 1 is dispersed in compound VII containing a strong acid resin, and heated and stirred at 80° C. for 15 h to obtain a further modified composite positive electrode material 1;
[0251] 2. The composite positive electrode material 1 prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is applied to aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0252] Preparation of electrolyte 7 samples
[0253] Preparation method and electrolyte formula are the same as those of Example 1 Electrolyte 1 Sample
[0254] Preparation of experimental battery 7 samples
[0255] 1. The preparation of negative electrode sheets and the assembly of bare cells are the same as in Example 1;
[0256] 2. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, and then cool it to below 40°C and inject the prepared electrolyte 7 sample to obtain the experimental battery 7 sample, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0257] Example 8
[0258] Preparation of modified in-situ coated sodium ion layered oxide cathode materials
[0259] Reaction 1
[0260]
[0261] 1. The sodium ion layered oxide positive electrode material 2 coated with polymer II obtained in Example 2 is dispersed in compound VIII containing a strong acid resin, and heated and stirred at 80° C. for 12 h to obtain a further modified composite positive electrode material 2;
[0262] 2. The composite positive electrode material 2 prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is applied to aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0263] Preparation of electrolyte 8 samples
[0264] Preparation method and electrolyte formula are the same as those of Example 2 Electrolyte 2 Sample
[0265] Preparation of experimental battery 8 samples
[0266] 1. The preparation of negative electrode sheets and the assembly of bare cells are the same as in Example 1;
[0267] 2. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, and then cool it to below 40°C and inject 8 samples of the prepared electrolyte to obtain 8 samples of experimental batteries, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0268] Example 9
[0269] Preparation of modified in-situ coated sodium ion layered oxide cathode materials
[0270] Reaction 1
[0271]
[0272] 1. The sodium ion layered oxide positive electrode material 3 coated with polymer III obtained in Example 3 is dispersed in compound IX containing a strong acid resin, and heated and stirred at 80° C. for 24 h to obtain a further modified composite positive electrode material 3;
[0273] 2. The composite positive electrode material 3 prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is applied to aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0274] Preparation of electrolyte 9 samples
[0275] Preparation method and electrolyte formula are the same as those of Example 3 Electrolyte 3 Sample
[0276] Preparation of experimental battery 9 samples
[0277] 1. The preparation of negative electrode sheets and the assembly of bare cells are the same as in Example 1;
[0278] 2. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, cool it to below 40°C, inject the prepared electrolyte 9 samples, and obtain 9 experimental battery samples, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0279] Example 10
[0280] Preparation of modified in-situ coated sodium ion layered oxide cathode materials
[0281] Reaction 1
[0282]
[0283] 1. The sodium ion layered oxide positive electrode material 4 coated with polymer IV obtained in Example 4 is dispersed in the compound X containing a strong acid resin, and heated and stirred at 80° C. for 24 h to obtain a further modified composite positive electrode material 4;
[0284] 2. The composite positive electrode material 4 prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is applied to aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0285] Preparation of 10 samples of electrolyte
[0286] Preparation method and electrolyte formula are the same as those of Example 4 Electrolyte 4 Sample
[0287] Preparation of 10 experimental battery samples
[0288] 1. The preparation of negative electrode sheets and the assembly of bare cells are the same as in Example 1;
[0289] 2. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, and then inject 10 samples of the prepared electrolyte after cooling to below 40°C to obtain 10 samples of the experimental battery, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0290] Embodiment 11
[0291] Preparation of modified in-situ coated sodium ion layered oxide cathode materials
[0292] Reaction 1
[0293]
[0294] 1. The sodium ion layered oxide positive electrode material 5 coated with polymer V obtained in Example 5 is dispersed in compound XI containing strong acid resin, heated and stirred at 80° C. for 18 h to obtain a further modified composite positive electrode material 5;
[0295] 2. The composite positive electrode material 5 prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is applied to aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0296] Preparation of electrolyte 11 samples
[0297] Preparation method and electrolyte formula are the same as those of Example 5 Electrolyte 5 Sample
[0298] Preparation of experimental battery 11 samples
[0299] 1. The preparation of negative electrode sheets and the assembly of bare cells are the same as in Example 1;
[0300] 2. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, and then inject the prepared electrolyte 11 sample after cooling to below 40°C to obtain the experimental battery 11 sample, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0301] Example 12
[0302] Preparation of modified in-situ coated sodium ion layered oxide cathode materials
[0303] Reaction 1
[0304]
[0305] 1. The sodium ion layered oxide positive electrode material 6 coated with polymer VI obtained in Example 6 is dispersed in compound XII containing a strong acid resin, and heated and stirred at 80° C. for 16 h to obtain a further modified composite positive electrode material 6;
[0306] 2. The composite positive electrode material 6 prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is applied to aluminum foil. After drying, rolling and die-cutting, a positive electrode sheet is obtained.
[0307] Preparation of electrolyte 12 samples
[0308] Preparation method and electrolyte formula are the same as those of Example 6 Electrolyte 6 Sample
[0309] Preparation of experimental battery 12 samples
[0310] 1. The preparation of negative electrode sheets and the assembly of bare cells are the same as in Example 1;
[0311] 2. Place the bare battery cell in an aluminum-plastic film outer package, vacuum bake it at 90°C for 12 hours, and then inject the prepared electrolyte 12 samples after cooling to below 40°C to obtain the experimental battery 12 samples, followed by packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0312] Comparative Example 1
[0313] 1. 2 mol of sodium ion layered oxide positive electrode active material (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 ) is dispersed in chloroform and stirred continuously to make the positive electrode material uniformly dispersed in the solvent;
[0314] 2. Then, 6 mol of pyrrole monomer was dispersed in dichloromethane and stirred for 1.5 h to fully disperse the pyrrole monomer. After dispersion, 0.3 mol of initiator boron trifluoride ether (BF 3 ·OEt 2 ) and continue stirring to fully dissolve;
[0315] 3. Mix the positive electrode material dispersion and the pyrrole monomer dispersion, stir evenly, control the temperature at 10°C, react for 6 hours, filter, wash and dry the reaction mixture to obtain a sodium ion layered oxide positive electrode material comparison sample 1 coated with polypyrrole.
[0316] 5. The composite positive electrode material comparison sample 1 prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is applied to aluminum foil. After drying, rolling and die-cutting, a comparison sample positive electrode sheet 1 is obtained.
[0317] The preparation of negative electrode material and comparative sample battery 1 is the same as that of Example 1
[0318] Comparative Example 2
[0319] 1. 2 mol of sodium ion layered oxide positive electrode active material (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 ) is dispersed in chloroform and stirred continuously to make the positive electrode material uniformly dispersed in the solvent;
[0320] 2. Then, 6 mol of methyl methacrylate monomer was dispersed in chloroform and stirred for 1.5 h to fully disperse the methyl methacrylate monomer. After dispersion, 0.3 mol of initiator azobisisobutyronitrile was added and stirred continuously to fully dissolve it.
[0321] 3. Mix the positive electrode material dispersion and the methyl methacrylate monomer dispersion, stir evenly, control the temperature at 55° C., react for 3 hours, filter, wash and dry the reaction mixture to obtain a sodium ion layered oxide positive electrode material comparison sample 2 coated with polypyrrole.
[0322] 5. The composite positive electrode material comparison sample 2 prepared above is mixed with the conductive agent SP, the binder PVDF and the solvent NMP, and the theoretical solid content is controlled to 70%. By sufficient stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is applied to aluminum foil. After drying, rolling and die-cutting, a comparison sample positive electrode sheet 2 is obtained.
[0323] The preparation of negative electrode material and comparative sample battery 2 is the same as that of Example 2
[0324] Comparative Example 3
[0325] Using uncoated sodium layered oxide positive electrode active material (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 ) is mixed with a conductive agent SP, a binder PVDF and a solvent NMP, and the theoretical solid content is controlled to be 70%. By fully stirring, a uniformly dispersed positive electrode slurry is prepared, and the slurry is applied to an aluminum foil. After drying, rolling and die-cutting, a comparative positive electrode sheet 3 is obtained.
[0326] The preparation of negative electrode material and comparative sample battery 3 is the same as that of Example 3
[0327] In order to verify the air stability of the sodium-electrolyte layered oxide positive electrode material in situ coated with the newly synthesized monomer in the present invention, the composite positive electrode materials prepared in Examples 1 to 6 and the positive electrode material of Comparative Example 3 were exposed to an air environment (temperature 25°C, dew point -3.89°C) for 12 hours and then homogenized as positive electrode active materials (considering the water absorption of the binder and the solvent, the homogenization was carried out in a dry room environment, temperature: 20°C, dew point -46.5°C), and the slurry state was observed. The homogenization ratio was the same as in Example 1.
[0328] Table 1. State of the homogenized slurry of positive electrode materials in Examples 1 to 6 and Comparative Example 3
[0329] Sample name Slurry state Example 1 Composite positive electrode material Ungelled Example 2 Composite positive electrode material Ungelled Example 3 Composite positive electrode material Ungelled Example 4 Composite positive electrode material Ungelled Example 5 Composite positive electrode material Ungelled Example 6 Composite positive electrode material Ungelled Comparative Example 3 Positive Electrode Material gel
[0330] In order to verify the electrochemical performance of the composite positive electrode material prepared by the present invention, the first efficiency and the fractional capacity (the battery cell design capacity is 1.12Ah) of Examples 1 to 12 and Comparative Examples 1 to 3 were compared, and the room temperature cycle performance and rate performance were further tested in a constant temperature room.
[0331] 1. Room temperature cycle performance test conditions
[0332] Test temperature: 25℃;
[0333] Voltage range: 2-4.0V
[0334] Charge / discharge rate: 1C
[0335] 2. Rate performance test conditions
[0336] Test temperature: 25℃;
[0337] Voltage range: 2-4.0V
[0338] Test rate: 0.2C / 0.5C / 1C / 2C / 3C / 5C
[0339] Table 2: First effect and fractional capacity of Examples 1 to 12 and Comparative Examples 1 to 3
[0340]
[0341]
[0342] According to the first effect and fractional capacity obtained from the test, the coated positive electrodes used in Examples 1 to 12 and Comparative Examples 1 to 2 have higher first effect and fractional capacity than the uncoated positive electrode material of Comparative Example 3, indicating that the polymer coating can effectively inhibit the side reaction between the positive electrode and the electrolyte in the electrochemical process and reduce the loss of active sodium. Examples 1 to 12 use the positive electrodes prepared by the newly synthesized conductive and ion-conducting dual-functional coating layer of the present invention. Compared with the composite positive electrode coated with a single conductive or ion-conducting polymer layer in Comparative Examples 1 to 2, the positive electrode with a dual-functional coating layer prepared by the present invention has a higher first effect and fractional discharge capacity. On the one hand, it shows that the composite positive electrode prepared by the present invention has better stability, and on the other hand, it shows that the composite positive electrode prepared by the present invention has better electron transmission and ion transmission capabilities, and can avoid capacity loss caused by polarization. In addition, compared with Examples 1 to 6, Examples 7 to 12 have certain beneficial effects on improving the first effect and capacity of the battery cell by further modifying the surface dual-functional coating layer.
[0343] Table 3 Room temperature cycle capacity and retention rate of Examples 1 to 12 and Comparative Examples 1 to 3
[0344]
[0345]
[0346] According to the room temperature cycle capacity and retention rate of the batteries in Examples 1 to 12 and Comparative Examples 1 to 3, the coated positive electrode can effectively inhibit the positive electrode side reactions and structural collapse during the cycle process. However, compared with the composite positive electrode coated with a simple conductive polymer or ion-conducting polymer layer in Comparative Examples 1 to 2, the present invention maintains a high ion and electron transmission capacity of the composite positive electrode by coating with an ion and electron dual-conducting polymer layer, reduces polarization, and provides a certain amount of active sodium ions through the sodium sulfonate of the coating layer, achieving a certain sodium supplementation effect, so the sample battery has a higher capacity retention. At the same time, according to Examples 7 to 12, by further modifying the surface coating layer of the coated positive electrode material prepared by the present invention, the double confinement of transition metal ions is achieved through polymer coating and surface anchoring, which strengthens the inhibition of the side reaction of transition metal ion dissolution and the collapse of the positive electrode structure during the cycle, and further improves the cycle life of the battery.
[0347] Table 4 Rate test data of sample batteries in Examples 1 to 12 and Comparative Examples 1 to 3
[0348]
[0349]
[0350] According to the rate discharge and rate charge capacity retention rates of Examples 1 to 12 and Comparative Examples 1 to 3, the rate performance of the battery can be improved to a certain extent after being coated with a conductive polymer or ion-conducting polymer layer in Comparative Examples 1 to 2 compared with Comparative Example 3, but the battery prepared by the composite positive electrode coated with an ion and electron double conductive layer has better rate performance than Examples 1 to 12 of the present invention. According to the rate performance of Examples 1 to 6 and Examples 7 to 12, the rate performance is also slightly improved by further modifying the surface of the coating layer.
[0351] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A polymer monomer for in-situ coating of a positive electrode material, having the structure shown in compound A: In compound A, R1 is a C1-C3 alkyl group, n is the degree of polymerization, and n=6000-10000.
2. The polymer monomer for in-situ coating of positive electrode materials according to claim 1, characterized in that: R1 is -CH3, -CH2CH3, -CH2F, -CH2OCH3, -CH2CH2F or -CH(CH3)2.
3. The method for preparing the polymerized monomer for in-situ coating of the positive electrode material according to claim 1, comprising the following steps: A) mixing compound B and di-tert-butyl dicarbonate in an alcohol solvent, stirring to react, to obtain compound C; B) dispersing compound C and zinc chloride in an aprotic solvent, adding hydrochloric acid dropwise, heating and reacting under stirring conditions to obtain compound D; C) dispersing compound D in a sodium sulfite aqueous solution, heating the mixture in a first reaction vessel to obtain a mixture containing compound E, then transferring the mixture containing compound E to a second reaction vessel, dropping trifluoroacetic acid into the mixture, and continuously stirring to react, to obtain compound A; 4. The preparation method according to claim 3, characterized in that: The alcohol solvent in step A) is methanol; The reaction temperature in step A) is 40-50° C., and the reaction time in step A) is 1-3 hours.
5. The preparation method according to claim 3, characterized in that: The aprotic solvent in step B) is one or more of ether, carbon tetrachloride, dimethyl sulfoxide and acetone; The reaction temperature in step B) is 30-50° C., and the reaction time in step B) is 2-6 hours.
6. The preparation method according to claim 3, characterized in that: In the step C), the temperature for the reaction of compound D with sodium sulfite is 180-220° C., and the reaction time is 2-5 hours; The reaction temperature of the mixture containing compound E and trifluoroacetic acid in step C) is 180-220° C. and the reaction time is 1-3 hours.
7. An in-situ coated sodium ion positive electrode material, comprising a sodium ion layered oxide positive electrode material and a coating layer coated on the surface of the sodium ion layered oxide; The coating layer includes a compound shown in Formula I: In formula I, R1 is a C1-C3 alkyl group, R2 is a substituted or unsubstituted C1-C5 alkyl group, and n is the degree of polymerization, n=6000-10000.
8. A method for preparing an in-situ coated sodium ion positive electrode material as claimed in claim 7, comprising the following steps: a) mixing a sodium ion layered oxide dispersion and a compound A dispersion to perform an in-situ polymerization reaction to obtain an intermediate; The sodium ion layered oxide dispersion comprises a sodium ion layered oxide positive electrode material and an inert organic solvent; The compound A dispersion comprises compound A, an initiator, a catalyst and an inert organic solvent; b) mixing the intermediate, R2-NH2 and a strong acid resin, and modifying them to obtain an in-situ coated sodium ion positive electrode material.
9. The preparation method according to claim 5, characterized in that: The molar ratio of the sodium ion layered oxide positive electrode material to compound A is 1:(2-6); The temperature of the in-situ polymerization in step A) is 0 to 25° C., and the time of the in-situ polymerization in step A) is 3 to 8 hours; The modification temperature in step B) is 75 to 90° C., and the modification time in step B) is 12 to 24 hours.
10. A positive electrode, comprising a current collector and a positive electrode active material layer composited on the surface of the current collector, wherein the positive electrode active material layer comprises the in-situ coated sodium ion positive electrode material according to claim 7 or the in-situ coated sodium ion positive electrode material prepared by the preparation method according to any one of claims 8 to 9.
11. A sodium ion battery comprising the positive electrode according to claim 10.
Citation Information
Patent Citations
Conductive adhesive containing conductive macromolecules and preparation method thereof
CN103666363A
Coated sodium ion battery positive electrode material and preparation method thereof
CN116864645A